Effect of twins on scratching behavior of nanotwinned diamond: A molecular dynamics simulation - Chen, Junyun; Zhang, Wanxue; Tong, Ke (Applied surface science, 2023)
[Display omitted] •Twins enhance the plasticity of diamond and relieve the stress concentration.•Twins lead to change of the distribution and type of dislocation.•The damage of nanotwinned diamond is caused by amorphization and detwinning. Nanotwinned diamond is a promising candidate material for cutting tools, high-pressure physics, and other fields due to its excellent properties of much higher hardness and toughness as compared to single-crystal diamond. Remarkable achievements have been achieved in understanding the mechanical properties and deformation mechanism when nanotwinned diamonds are subject to compression, fracture, or indentation. In this work, the response of nanotwinned diamonds under scratching was studied using molecular dynamics simulation. The morphology of chips and subsurface damage, the distribution of temperature and stress, the formation process of subsurface damage, and the plastic deformation mechanism were systematically investigated. Compared with single-crystal diamonds, more obvious plastic deformation was found in nanotwinned diamonds. Unlike single crystal diamonds, in which perfect dislocations mainly slipped on those {111} planes inclined to the scratching direction, for the nanotwinned diamond, partial dislocation was found to be the dominant dislocation type and only slipped on the {111} planes parallel to the twin boundaries. Furthermore, detwinning was also observed during subsurface damage formation besides amorphism. These results show the mechanical response of nanotwinned diamonds under scratching and provide theoretical guidance for the application of nanotwinned diamonds.